The effect of vaginal evening primrose capsule on cervical ripening in nulliparous women with post-term pregnancy: A clinical trial - Shadab Shahali; Fatemeh Khatami; Zahra Abbaspoor; Bahman Gheraghian (Mashhad University of Medical Sciences, 2018)
Introduction: post term pregnancy is associated with maternal and fetal complications, including sudden death of the fetus and low Apgar score after birth. Evening primrose oil has been used for cervical ripening. Despite the effects of evening primrose oil on prostaglandin precursor levels and the well-established role of prostaglandins in the reconstruction of cervical matrix. This study was performed with aim to evaluate the effect of vaginal consumption of evening primrose oil on cervical ripening in nulliparous women with post-term pregnancy. Methods: This randomized clinical trial study was conducted on 60 pregnant women with post-term pregnancy who referred to the maternity of Ahvaz Sina Hospital in 2017. The study groups consisted of 2 groups: vaginal capsule of 1000 mg of evening primrose oil and placebo. Drug was administered after induction of labor with 10 unit oxytocin. In the intervention group, one vaginal capsule of 1000 mg of evening primrose oil and in the control group, gelatin capsule as similar as the drug were used. Then, the induction of labor was started with oxytocin with similar dose (10 unit in 1000 cc serum ringer) in both groups. Cervical ripening was measured based on regular examination (every one hour). Data were collected by demographic questionnaire, timing, and bishop-score checklist. Data were analyzed by SPSS software (version 22) and independent t-test and Chi-square test. P<0.05 was considered statistically significant. Results: The duration of the latent phase in both groups was 9-10.5 hour. The duration of latent phase (p=0.003) and bishop score (p=0.01) had significant difference between the intervention group and the placebo group; it means more cervical ripening in the intervention group. At second stage of measurement, bishop score ≥7 was 90% in the intervention group and 60% in the control group that was significantly more in the intervention group (P=0.01). However, no significant difference between the two groups in terms of the duration of the active phase, progression rate, severity of pain, and volume of bleeding. Conclusion: The vaginal use of evening primrose oil reduces the duration of the latent phase and has a positive effect on the cervical ripening and Bishop score.